The Immunomodulatory Effect of Recombinant Exotoxin A of Pseudomonas Aeruginosa on Dendritic Cells Extracted from Mice Spleen - Mohammad Hossein Karimi; Aziz Japoni; Manouchehr Rasouli; Salimeh Ebrahimnezhad (Fasa University of Medical Sciences, 2014)
Background & Objective: Dendritic cell (DC) is as a key cell in activation of immune response against microbes and disease. Therefore, the effect of recombinant exotoxin A of Pseudomonas aeruginosa on the maturity and the activation of DCs was evaluated in this study. Materials & Methods: Recombinant exotoxin A was produced from Pseudomonas aeruginosa DNA. MTT assay was used to evaluate the cytotoxicity of this protein on DCs. The expression of co-stimulatory molecules CD40, CD86, and MHCΠ was evaluated by flow cytometry. Moreover, the effect of this antigen (Ag) on T-cell proliferation was evaluated using Mixed Lymphocyte Reaction (MLR) assay and the secretion of IL-4 and IFN- γ. Secretion of IL-12 by DCs was measured with Enzyme-Linked Immunosorbent Assay (ELISA) method. The data were collected and analyzed with one way ANOVA test. Results: Recombinant exotoxin A had no effect on DCs viability. In addition, expression of CD40, CD86, and MHCΠ did not change significantly compared to the negative control cells. Moreover, T-cells proliferation was decreased significantly at the concentration of 0.1µg/ml of this Ag. The secretion of IL-12 was increased by DCs, in contrast the secretion of IL-4 and IFN-γ in MLR supernatant did not decrease significantly. Conclusion: Exotoxin A decreases the proliferation of T-cells and also leads to a change in the pattern of cytokine secretion of immune cells.